PENGEMBANGAN MEDIA PEMBELAJARAN PALIPA PADA MATERI MENGENALI SIMBOL PANCASILA UNTUK SISWA KELAS II SEKOLAH DASAR - Wedar Puji Marta, Trias; Abdul Aziz Hunaifi; Rian Damariswara (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is motivated by the fact that in learning Civics, the material is recognizing Pancasila symbols, many students do not understand the material, this can be seen when students cannot answer questions given by the teacher. Students' lack of understanding in the material of recognizing Pancasila symbols is also caused by teachers using more lecture methods. This can make students not interested in the material presented by the teacher. The lack of development of the media used in learning activities regarding recognizing Pancasila symbols can reduce students' interest in learning. As a solution to the problems above, it is necessary to develop the PALIPA learning media "Folding Board". PALIPA is an innovative new media that attracts the interest of class II students to recognize the Pancasila symbols. The objectives of this research and development are: (1) To determine the validity of the Palipa learning media on the material of recognizing Pancasila symbols for class II elementary school students. (2) To find out the practicality of Palipa learning media on the material of recognizing Pancasila symbols for class II elementary school students. (3) To determine the effectiveness of the Palipa learning media in recognizing Pancasila symbols for class II elementary school students. This research uses the (R&D) (Research and Development) method with the ADDIE model which consists of 5 steps, namely (1) Analysis, (2) Design, (3) Development, (4) Implementation ( Implementation), and (5) Evaluation. The subjects of this research were 15 class II students at SDN Setonorejo 1 and 5 students at SDN Setonorejo 2. The data analysis techniques used are qualitative descriptive analysis and quantitative descriptive analysis. The results of this research show that. (1) The validation results obtained from media validators reached a percentage of 86% and material validators reached a percentage of 90%. So the validity results of the Palipa learning media on the material for recognizing Pancasila symbols obtained an average percentage of 88% with very valid criteria. (2) The average results of the teacher response questionnaires at SDN Setonorejo 1 and Setonorejo 2 reached a percentage of 98% and the results of the student response questionnaire reached a percentage of 92%. So the practical results of the Palipa learning media in the material of recognizing Pancasila symbols obtained very practical criteria. (3) The results of the analysis of evaluation questions (post-test) obtained an average percentage of 90.9% with very effective criteria.It can be concluded that the Palipa learning media on the material recognizing Pancasila symbols for grade II elementary school students that was developed is declared valid, practical and effective. So it is suitable for use in the learning process.